A novel partial resuscitative endovascular balloon aortic occlusion device that can be deployed in zone 1 for more than 2 hours with minimal provider titration. Issue 3 (22nd March 2021) - Kemp, Michael T.; Wakam, Glenn K.; Williams, Aaron M.; Biesterveld, Ben E.; O'Connell, Rachel L.; Vercruysse, Claire A.; Chtraklin, Kiril; Russo, Rachel M.; Alam, Hasan B.
Abstract : BACKGROUND: Hemorrhage is a leading cause of mortality in trauma. Resuscitative endovascular balloon occlusion of the aorta (REBOA) can control hemorrhage, but distal ischemia, subsequent reperfusion injury, and the need for frequent balloon titration remain problems. Improved device design can allow for partial REBOA (pREBOA) that may provide hemorrhage control while also perfusing distally without need for significant provider titration. METHODS: Female Yorkshire swine (N = 10) were subjected to 40% hemorrhagic shock for 1 hour (mean arterial pressure [MAP], 28–32 mm Hg). Animals were then randomized to either complete aortic occlusion (ER-REBOA) or partial occlusion (novel pREBOA-PRO) without frequent provider titration or distal MAP targets. Detection of a trace distal waveform determined partial occlusion in the pREBOA-PRO arm. After 2 hours of zone 1 occlusion, the hemorrhaged whole blood was returned. After 50% autotransfusion, the balloon was deflated over a 10-minute period. Following transfusion, the animals were survived for 2 hours while receiving resuscitation based on objective targets: lactated Ringer's fluid boluses (goal central venous pressure, ≥ 6 mm Hg), a norepinephrine infusion (goal MAP, 55–60 mm Hg), and acid-base correction (goal pH, >7.2). Hemodynamic variables, arterial lactate, lactate dehydrogenase, aspartate aminotransferase, and creatinine levels were measured. RESULTS: All animals survived throughout the experiment, with similar increase in proximal MAPs in both groups. Animals that underwent partial occlusion had slightly higher distal MAPs. At the end of the experiment, the partial occlusion group had lower end levels of serum lactate ( p = 0.006), lactate dehydrogenase ( p = 0.0004) and aspartate aminotransferase ( p = 0.004). Animals that underwent partial occlusion required less norepinephrine ( p = 0.002), less bicarbonate administration ( p = 0.006), and less fluid resuscitation ( p = 0.042). CONCLUSION: Improved design for pREBOA can decrease the degree of distal ischemia and reperfusion injury compared with complete aortic occlusion, while providing a similar increase in proximal MAPs. This can allow pREBOA zone-1 deployment for longer periods without the need for significant balloon titration.